Co-Regulation of Long Non-Coding RNAs with Allele-Specific Genes in Wheat Responding to Powdery Mildew Infection - Weiguo Hu; Guanghao Wang; Siwen Wang; Xiaojun Nie; Changyou Wang; Yajuan Wang; Hong Zhang; Wanquan Ji (Agronomy, 2020)
Powdery mildew (caused by Blumeria graminis f. sp. tritici; Bgt) is an important fungal disease of wheat (Triticum aestivum) worldwide, and results in significant crop damage in epidemic years. Understanding resistance mechanisms could have undoubted benefits in controlling disease and minimizing crop losses. The recent explosion in genomic knowledge and the discovery of noncoding RNAs have led to the idea that long ncRNAs (lncRNAs) might be key regulators of protein-coding gene expression. However, in-depth functional analyses of lncRNAs in wheat remain limited. Here, we evaluated the possible role of lncRNAs in regulating functional genes in wheat responding to Bgt pathogen, using genome-wide transcriptome data and quantitative RT-PCR. Our results demonstrated that both long intron ncRNAs (linncRNA) and long intergenic ncRNAs (lincRNAs) play roles in regulating allele-specific genes, including transcription factors, both positively and negatively. The correlation of expression between lincRNAs and flanking functional genes increased as the spacing distance decreased. Co-expression of microRNAs, their target lncRNA and target functional genes showed that lincRNA interacted competitively with functional genes via miRNA regulation. These results will be beneficial for further dissecting molecular mechanisms of lncRNAs functions at the transcriptional and post-transcriptional levels in wheat.